[11C]‐(+)‐PHNO PET imaging of dopamine D2/3 receptors in Parkinson's disease with impulse control disorders. Issue 2 (14th January 2015) - Payer, Doris E.; Guttman, Mark; Kish, Stephen J.; Tong, Junchao; Strafella, Antonio; Zack, Martin; Adams, John R.; Rusjan, Pablo; Houle, Sylvain; Furukawa, Yoshiaki; Wilson, Alan A.; Boileau, Isabelle; et al.
Abstract Dopamine agonist medications with high affinity for the D3 dopamine receptor are commonly used to treat Parkinson's disease, and have been associated with pathological behaviors categorized under the umbrella of impulse control disorders (ICD). The aim of this study was to investigate whether ICD in Parkinson's patients are associated with greater D3 dopamine receptor availability. We used positron emission tomography (PET) radioligand imaging with the D3 dopamine receptor preferring agonist [11C]‐(+)‐propyl‐hexahydro‐naphtho‐oxazin (PHNO) in Parkinson's patients with (n = 11) and without (n = 21) ICD, and age‐, sex‐, and education‐matched healthy control subjects (n = 18). Contrary to hypotheses, [11C]‐(+)‐PHNO binding in D3‐rich brain areas was not elevated in Parkinson's patients with ICD compared with those without; instead, [11C]‐(+)‐PHNO binding in ventral striatum was 20% lower (P = 0.011), correlating with two measures of ICD severity (r = −0.8 and −0.9), which may reflect higher dopamine tone in ventral striatum. In dorsal striatum, where [11C]‐(+)‐PHNO binding is associated with D2 receptor levels, [11C]‐(+)‐PHNO binding was elevated across patients compared with controls. We conclude that although D3 dopamine receptors have been linked to the occurrence of ICD in Parkinson's patients. Our findings do not support the hypothesis that D3 receptor levels are elevated in Parkinson's patients with ICD. We also did not find ICD‐related abnormalities in D2 receptor levels. Our findings argue against the possibility that differences in D2/3 receptor levels can account for the development of ICD in PD; however, we cannot rule out that differences in dopamine levels (particularly in ventral striatum) may be involved. © 2015 International Parkinson and Movement Disorder Society